2017
DOI: 10.1590/0100-3984.2015.0215
|View full text |Cite
|
Sign up to set email alerts
|

Perineural spread of malignant head and neck tumors: review of the literature and analysis of cases treated at a teaching hospital

Abstract: Perineural tumor spread refers to the migration of tumor cells along nerve tissues. It worsens the prognosis, increases the recurrence rate, and diminishes 5-year survival by up to 30%. It is an important finding on imaging tests employed in the staging of patients with head and neck cancers, because it cannot be assessed by the surgeon alone. Nevertheless, it is frequently overlooked. In this study, we reviewed the literature regarding the imaging and pathophysiological aspects of this type of dissemination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…10 In the absence of symptoms such as pain, burning sensation, or paresthesias, which have been reported to be present in up to 60% of patients with PNS, PNS is less likely. 8 MRI has been shown to have a detection rate in large nerve PNS of greater than 95%, 11 and in our patient, it showed no enlargement or enhancement of nerves or other findings suggestive of PNS. However, absence of MRI findings does not definitively rule out PNS.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…10 In the absence of symptoms such as pain, burning sensation, or paresthesias, which have been reported to be present in up to 60% of patients with PNS, PNS is less likely. 8 MRI has been shown to have a detection rate in large nerve PNS of greater than 95%, 11 and in our patient, it showed no enlargement or enhancement of nerves or other findings suggestive of PNS. However, absence of MRI findings does not definitively rule out PNS.…”
Section: Discussionsupporting
confidence: 52%
“…PNS is rarely associated with melanoma and more commonly associated with other cancers of the skin such as squamous cell carcinoma, adenoid cystic carcinoma, and lymphoma, among others. 8 Additionally, without any evidence of melanoma metastases to the head and neck, it would be very rare for first and new metastases to appear as PNS to cranial nerve VI. PNS most commonly occurs along branches of the trigeminal nerve, or the facial nerve in cases of metastases to the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNTS can be subtle on imaging, and it usually requires careful evaluation over multiple sequences. 42 It has been suggested that because of this and perhaps also because of inadequate training of radiologists to look for it, PNTS on MRI might be missed frequently. 43 The T1-weighted sequence is often referred to as the head and neck anatomic sequence because it results in high signal intensity of fat-containing structures.…”
Section: Clinical Significancementioning
confidence: 99%
“…Recent advances in computed tomography (CT) and magnetic resonance imaging techniques have increased the importance of imaging studies in the evaluation of diseases that affect the head and neck ( 5 - 10 ) . Although CT scans are used routinely in anatomical evaluations of the paranasal sinuses, a recent study showed that 75% of radiological reports add little value in terms of informing therapeutic decisions ( 1 , 11 ) .…”
Section: Introductionmentioning
confidence: 99%